Migration of the Industrial Wastewater in Fractured Rock Masses Based on the Thermal-Hydraulic-Mechanical Coupled Model - Yanan Gao; Peng Guo; Zetian Zhang; Minghui Li; Feng Gao (Geofluids)
Industrial wastewater may have a long-time effect on the environment and human life as it goes underground and causes serious pollution continuously. To have a well understanding of the migration of such wastewater is a basic task for industrial wastewater treatment as well as industrial design. To study the migration mechanism of industrial wastewater in rock formations, the governing equations such as mechanics, seepage, heat, and mass transfer are reviewed, referenced, and proposed. The thermal (T)-hydraulic (H)-mechanical (M) coupled model of the multimedia of matrix-fault and matrix-fracture-fault is established. The influence of the fault and the fractures on the pressure distribution and contaminant migration is analyzed. The influence of fault length, width, dip angle, permeability, and temperature of wastewater on contaminant migration is parametrically studied. The following results can be obtained. (1) The fracture quantitively affects the concentration distribution, while the fault dominates the concentration distribution and contaminant migration. (2) The migration of the contaminants can be geometrically divided into 3 zones along the direction of the fault: the saturation zone, the rapid diffusion zone, and the concentration decrease zone. (3) There is a peak of the concentration along the bottom of the model. The position of the peak is the projection of the endpoint of the fault. (4) The fault length has the most significant effect on contaminant accumulation. The temperature of the wastewater has the minimum effect on the contaminant accumulation. (5) The accumulation of concentrations can be divided into 2 stages, the slow growth stage (before 20 years) and the rapid growth stage (after 20 years). The main channel of contaminant migration in the slow growth stage is a fault. During the rapid growth stage, the contaminants penetrate through the rock matrix as well as the fault.